2006
DOI: 10.1051/0004-6361:20054087
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative structures of diffuse molecular gas

Abstract: Aims. Specific chemical signatures of the intermittent dissipation of turbulence were sought in diffuse molecular clouds. Methods. We observed HCO + (1−0) lines and the two lowest rotational transitions of 12 CO and 13 CO with an exceptional signal-tonoise ratio in the translucent environment of low-mass dense cores, where turbulence dissipation is expected to take place. Some of the observed positions belong to a new kind of small-scale structure identified in CO(1−0) maps of these environments as the locus o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 37 publications
1
46
0
Order By: Relevance
“…2) Dark clouds have haloes (Wannier et al 1993;Bensch 2006) and it has been suggested that the molecules supposedly seen in diffuse clouds are actually located around and exchanging material with dark clouds (Federman & Allen 1991); this may be true in some cases, but complex trace molecules are also seen along sightlines which are quite well separated from the nearest dark material . 3) Perhaps most promisingly, turnover within diffuse neutral gas due to turbulence, rapidly cycling material through a very dense phase, may provide for much faster formation of H 2 and trace species (Glover & Mac Low 2005;Falgarone et al 2005), establishing high molecular fractions from scratch on short timescales. The small fraction of neutral material which is observed to exist at very high pressure within diffuse clouds (Jenkins & Tripp 2001) and other aspects of small-scale structure in diffuse gas (Deshpande 2000) may perhaps also be understood in such terms.…”
Section: Lifetimes Of Diffuse Clouds and Their Hmentioning
confidence: 99%
“…2) Dark clouds have haloes (Wannier et al 1993;Bensch 2006) and it has been suggested that the molecules supposedly seen in diffuse clouds are actually located around and exchanging material with dark clouds (Federman & Allen 1991); this may be true in some cases, but complex trace molecules are also seen along sightlines which are quite well separated from the nearest dark material . 3) Perhaps most promisingly, turnover within diffuse neutral gas due to turbulence, rapidly cycling material through a very dense phase, may provide for much faster formation of H 2 and trace species (Glover & Mac Low 2005;Falgarone et al 2005), establishing high molecular fractions from scratch on short timescales. The small fraction of neutral material which is observed to exist at very high pressure within diffuse clouds (Jenkins & Tripp 2001) and other aspects of small-scale structure in diffuse gas (Deshpande 2000) may perhaps also be understood in such terms.…”
Section: Lifetimes Of Diffuse Clouds and Their Hmentioning
confidence: 99%
“…These pure velocity-structures do not follow those of dense gas: they tend to be parallel to the magnetic field orientation, they are associated with gas warmer (T kin > 25 K) than the bulk of the gas, and they bear chemical signatures of a warm chemistry that is not driven by UV photons (Falgarone et al 2006;Godard et al 2009). In one of these E-CVI structures, Plateau de Bure Interferometre (PdBI) observations disclose several substructures of intense velocity-shear at scales as small as 6 milliparsec (mpc) (Falgarone et al 2009, hereafter FPH09).…”
Section: Introductionmentioning
confidence: 97%
“…We thus conclude that the line arises in a gas phase In several respects, the existence of in the diffuse inter-ϩ CH stellar medium has remained for several decades among the most intractable puzzles in astrophysics (e.g., Bates & Spitzer 1951;Black & Dalgarno 1973;Black et al 1975;Falgarone et al 1995;Gredel et al 2002): needs H 2 to form but, once formed, it ϩ CH recombines rapidly with electrons or reacts with H 2 to form . However, the radiative association process…”
mentioning
confidence: 79%
“…The alternative ϩ CH formation route, , is highly endothermic (Crane et al 1995;Gredel 1997), and their line widths, of only a few kilometers per second, unambiguously ascribe them to the CNM. The pivotal role of H 2 in the chemistry leading to its formation, but also to its destruction, confines to the layers of the CNM where ϩ CH the visual extinction is less than a few tenths, i.e., where the H 2 abundance is nonnegligible but not dominant (Falgarone et al 1995). Moreover, there would have to be some fraction of this medium that has gas temperatures much greater than the typical 100 K of the CNM in order to provide a sufficient production rate of , implying a nonthermal energy source of some kind.…”
mentioning
confidence: 99%
See 1 more Smart Citation